Antidepressant Active Components of Bupleurum chinense DC-Paeonia lactiflora Pall Herb Pair: Pharmacological Mechanisms. (9th November 2022) - Lv, Shimeng; Zhao, Yifan; Wang, Le; Yu, Yihong; Li, Jiaxin; Huang, Yufei; Xu, Wenhua; Sun, Geqin; Dai, Weibo; Zhao, Tingting; Bi, Dezhong; Ma, Yuexiang; et al.
Abstract : Depression is a serious psychological disorder with a rapidly increasing incidence in recent years. Clinically, selective serotonin reuptake inhibitors are the main therapy. These drugs, have serious adverse reactions, however. Traditional Chinese medicine has the characteristics of multiple components, targets, and pathways, which has huge potential advantages for the treatment of depression. The antidepressant potential of the herbal combination of Bupleurum chinense DC (Chaihu) and Paeonia lactiflora Pall (Baishao) has been extensively studied previously. In this review, we summarized the antidepressant active components and mechanism of Chaihu-Baishao herb pair. We found that it works mainly through relieving oxidative stress, regulating HPA axis, and protecting neurons. Nevertheless, current research of this combined preparation still faces many challenges. On one hand, most of the current studies only stay at the level of animal models, lacking of sufficient clinical double-blind controlled trials for further verification. In addition, studies on the synergistic effect between different targets and signaling pathways are scarce. On the other hand, this preparation has numerous defects such as poor stability, low solubility, and difficulty in crossing the blood-brain barrier.